Libraries Canada, 2015-2016 Bibliotheques Canada. - Gale Group (Toronto, ON Grey House Publishing Canada, 2015)
Offers complete and comprehensive information on Canadian libraries, resource centers, business information centers, professional associations, regional library systems, archives, library schools and library technical programs.
section one. Public libraries -- section two. College & university libraries -- section three. Special libraries -- section four. Library services & resources -- section five. Library associations, consortia & groups.
Includes bibliographical references and indexes.
Parallel texts in English and French.
Keywords: Libraries -- Canada -- Directories